Funções da Música no Cinema: contribuições para a elaboração de estratégias composicionais - Andre Baptista (2007)
This text aims to organize a setting of concepts, ideas and functions of music in the audiovisual context and relate them to the most usual challenges that a composer has to overcome in the process of creation of a film score. The main objective is that such elements become a part of the theoretical tools that this professional has available, helping to increase his skills in the composition field and contributing in the choice of efficient strategies for the functional music.